The momentum relationship between rider and horse body parts and their contribution ratios from the total momentum from the take off stage to the double fence jump - Al-Samarae, M. S. K. (Journal of Physical Education and Sport, 2014)
This research has two goals. The first goal is to identify the values of momentum and the total parts of the body of the rider and the horse from take off to the double fence jump stages. The second goal is to identify the sharing ratio of the body parts momentum and the total momentum of the rider and the horse from take off to the double fence jump stages. A camera (Sony) with a speed of 25 images/s and a triple holder were set at a distance of 9 m from the fence. The camera lens was positioned perpendicular to the point of take off stage. The height of the camera was 1.55 m, whereas the height of the fence was 1.125 m. The procedures in the main experiment included the video recording of the three attempts of each rider. The best condition was then chosen based on the least time recorded for fence jumping without hitting or dropping the fence bar. Results showed that the momentum of the horse trunk is part of the total body momentum for the horse and rider because of his huge mass. The momentum of any other part of the rider (arms, legs, and trunk) is not part of the total body momentum of the horse and rider.